A visão atual da propriedade no Código Civil Brasileiro - Araujo, Juliana Frauches de (2015)
The purpose of this research is to analyse the steps which the property has gone through: from its state of nature, of an economic and absolute matter, to the presente day. Therefore, we still can understand in a broader view that, despite the properties, all the institutes evolved along with the needs of each society. Aiming a current reflection, the social role's question is opened, due to the risk of failure arising from new institutes. However, the philosophy behind this principle is adequate and nowadays is necessary regarding the best use of a space, providing, hence, progress